The Study of Salt Induced Viscoelastic Wormlike Micelles in Aqueous Systems of Mixed Anionic/Nonionic Surfactants - Shrestha, Rekha Goswami; Aramaki, Kenji (Journal of Nepal Chemical Society, 2009)
Formation of viscoelastic wormlike micelles in aqueous systems of mixed amino acid based anionic and nonionic surfactants in presence of salt is presented. N-dodecylglutamic acid (LAD) upon neutralization with L-Lysine in 1:2 mole ratio forms globular type of micelles above critical micelle concentration and the solution follows Newtonian fluid like behavior at 25ºC. The addition of tri(oxyethylene) nmonotetradecyl ether (C14EO3) to the semi-dilute aqueous solution of the LADLysine-2 induces one dimensional micellar growth and viscosity of solution increases. After a certain concentration of C14EO3 micelles get entangled and form a rigid network of wormlike micelles and viscosity increases by several orders of magnitude. The wormlike micellar solutions show a viscoelastic character and can be described the Maxwell mechanical model with a single stress relaxation. Rheological measurements have shown that zero shear viscosity (No) increases with the C14EO3 concentration gradually at first sharpl, and then finally decreases before phase separation.Keywords: nonionic surfactant, wormlike micelles, rheology, viscoelastic solutionsDOI: 10.3126/jncs.v23i0.2098J. Nepal Chem. Soc., Vol. 23, 2008/2009 Page: 65-73